If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -8) + -3(x + 2) = -24 Reorder the terms: 2(-8 + x) + -3(x + 2) = -24 (-8 * 2 + x * 2) + -3(x + 2) = -24 (-16 + 2x) + -3(x + 2) = -24 Reorder the terms: -16 + 2x + -3(2 + x) = -24 -16 + 2x + (2 * -3 + x * -3) = -24 -16 + 2x + (-6 + -3x) = -24 Reorder the terms: -16 + -6 + 2x + -3x = -24 Combine like terms: -16 + -6 = -22 -22 + 2x + -3x = -24 Combine like terms: 2x + -3x = -1x -22 + -1x = -24 Solving -22 + -1x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + -1x = -24 + 22 Combine like terms: -22 + 22 = 0 0 + -1x = -24 + 22 -1x = -24 + 22 Combine like terms: -24 + 22 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 4(3x+1)=7(8-2x) | | 3(2x-5)-2x=17 | | 13x-7x=24 | | 5x^2-33x+18= | | 8-5x=20-3 | | 6(14+2x)=36 | | 3x+10=6+x | | 20*x=1500 | | 40*x=1800 | | 4x-8=58-2x | | 19*x=6080 | | X^2+y^2-2xy+20x+10=0 | | 2(2x+4)=5x | | 3.5x=18 | | 18*x=1872 | | 11+15+3x=35-6x | | 4(x+6)=6(2x+2) | | (x^2-3xy+y^2)(2x-3y+2)=0 | | 2x^2+9x+81=0 | | 2x^2+9+81=0 | | 10534458=q | | 7a-2=11 | | 234*78=y | | 5x=34+1 | | -4(k-3)-(6-3k)=-2k | | 2.5-12=13 | | 5x+16x+2=0 | | .1(2m+3)-4m=1.1(2-3m)-2.4 | | 4(w-1)-(5w-8)=2w | | 2x^2-6x-3=0 | | x+214=389 | | 34.8k+.2(k-4)=1.2-9(2-3k) |